THE IMPACT OF CORPORATE GOVERNANCE ON THE TENDENCY OF SUSTAINABILITY REPORTING - Wijaya Triwacananingrum; Benedictus Daniel Pradipta See; Irene Monica Plesley; Jessica Tedja (Jurnal Pendidikan Akuntansi Indonesia, 2021)
This study aims to investigate the association between corporate governance and sustainability reports. We use binary logistic analysis in service industry companies listed on the IDX in 2018 to observe the relations between probability of the sustainability reporting and various factors related to corporate governance, including the capacity of the directors, the capacity of the commissioner, the capacity of the audit committees, and the independence of the directors. The result shows that there were significant differences between some of the corporate governance factors and the probability of reporting the sustainability report. Particularly in the capacity of the directors, where companies with higher number of board members and the frequency of board meetings have a higher probability of reporting sustainability reports. Then, the capacity of the audit committee, where companies with higher frequency of committee meetings have a higher probability to report sustainability reporting. This study adds information about corporate governance and sustainability reports. In addition, this study also provides empirical evidence and also provides suggestions that can be used by regulators in Indonesia on how the probability to report the sustainability reporting can be improved by enhancing the quality of corporate governance in the companies.